Regulation of gut microbiota-bile acids axis by probiotics in inflammatory bowel disease - Li, Lingfeng; Liu, Tianyu; Gu, Yu; Wang, Xinyu; Xie, Runxiang; Sun, Yue; Wang, Bangmao; Cao, Hailong (Frontiers in Immunology, 2022)
Inflammatory bowel disease (IBD) is characterized by chronic and relapsing inflammation of gastrointestinal tract, with steadily increased incidence and prevalence worldwide. Although the precise pathogenesis remains unclear, gut microbiota, bile acids (BAs), and aberrant immune response play essential roles in the development of IBD. Lately, gut dysbiosis including certain decreased beneficial bacteria and increased pathogens, and aberrant BAs metabolism have been reported in IBD. The bacteria inhabited in human gut have critical functions in bile acid biotransformation. Patients with active IBD have elevated primary and conjugated BAs and decreased secondary BAs, accompanied by the impaired transformation activities (mainly deconjugation and 7α-dehydroxylation) of gut microbiota. Probiotics have exhibited certain positive effects by different mechanisms in the therapy of IBD. This review discussed the effectiveness of probiotics in certain clinical and animal model studies that might involve in gut microbiota-BAs axis. More importantly, the possible mechanisms of probiotics on regulating gut microbiota-BAs axis in IBD were elucidated, which we focused on the elevated gut bacteria containing bile salt hydrolase or bile acid-inducible enzymes at genus/species level that might participate in the bile acid biotransformation. Furthermore, beneficial effects exerted by activation of bile acid-activated receptors on intestinal immunity were also summarized, which might partially explain the protect effects and mechanisms of probiotics on IBD. Therefore, this review will provide new insights into a better understanding of probiotics in the therapy targeting gut microbiota-BAs axis of IBD.